2014
DOI: 10.1177/0018726713519280
|View full text |Cite
|
Sign up to set email alerts
|

Service employees and self-verification: The roles of occupational stigma consciousness and core self-evaluations

Abstract: Despite the growing number and importance of service occupations, we know little about how jobholders’ perceptions of societal stigmas of service jobs influence their identification with and attitudes towards work. The present study presents a framework that accords key roles to research on occupational stigma consciousness and the verification of employees’ self-views (i.e. core self-evaluations) to understand employees’ responses to occupational stigmatization. Survey responses from call center employees rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
71
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 140 publications
(82 citation statements)
references
References 84 publications
6
71
0
Order By: Relevance
“…When others' treatment, feedback, or experiences are not aligned with individuals' self-views, self-verification theory predicts they feel uncertainty, a loss of control, and personally threatened. As a result, individuals whose self-views are challenged tend to behave defensively (Croyle, Sun, & Hart, 1997) and aggressively (e.g., Baumeister, Smart, & Boden, 1996), report lower levels of well-being (e.g., Frone, Russell, & Cooper, 1995) and less-positive attitudes toward their job and organization (e.g., Shantz & Booth, 2014;Wiesenfeld et al, 2007).…”
Section: Theoretical Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…When others' treatment, feedback, or experiences are not aligned with individuals' self-views, self-verification theory predicts they feel uncertainty, a loss of control, and personally threatened. As a result, individuals whose self-views are challenged tend to behave defensively (Croyle, Sun, & Hart, 1997) and aggressively (e.g., Baumeister, Smart, & Boden, 1996), report lower levels of well-being (e.g., Frone, Russell, & Cooper, 1995) and less-positive attitudes toward their job and organization (e.g., Shantz & Booth, 2014;Wiesenfeld et al, 2007).…”
Section: Theoretical Developmentmentioning
confidence: 99%
“…The self-view can be represented by a person's CSE (e.g., Shantz & Booth, 2014), a higher-order dispositional framework representing the fundamental evaluations people make about themselves and their functioning in the world (Judge, Locke, & Durham, 1997). Individuals high in CSE are confident, well adjusted, efficacious, and bring a positive frame to situations.…”
Section: Core Self-evaluation and Supervisor Underminingmentioning
confidence: 99%
“…Scholars suggest that service workers experience customer mistreatment as a blow to the ego or a threat to their self-esteem, which impacts service delivery (Dormann & Zapf, 2004;Shao & Skarlicki, 2014). The role of the self is especially salient in service work because it is often regarded as lowstatus, stigmatized work (Shantz & Booth, 2014). Older service workers-like their younger counterparts-may be exposed to customer mistreatment, which could impact their service delivery.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Judge and Bono's (2001) meta-analysis showed that, across 274 CSE, CONTEXT AND PERFORMANCE correlations between components of CSE and performance, there were positive, negative and non-significant relationships. Kacmar, Collins, Harris and Judge (2009) found evidence that the CSE-performance relationship may be negative in certain contexts, and a similar conclusion was drawn by Shantz and Booth (2014). A common theme in these studies is the role of leaders in creating environments that shape the enactment of dispositions in performance.…”
mentioning
confidence: 62%